Vulvovaginitis in childhood and adolescence in a gynecologist practice - Irina V. Karachentsova; Elena V. Sibirskaya; Mariya M. Fomina (Union of pediatricians of Russia, 2023)
Background. The study  of the etiology and pathogenesis of vulvovaginitis in different age periods of girls in order to preserve their reproductive health.  Objective. The aim of the study is - to identify risk factors  for the development of vulvovaginitis at different girls  age  periods.  Methods. Retrospective  analysis  of information  from  electronic  medical  records  of 100 girls  of various  ages with inflammatory diseases of the  vulva and vagina treated on an outpatient basis. Results. Risk factors  identified: children in the period of neonatality and infancy this is an incorrect conduct of hygiene measures due  to insufficient awareness of parents;  in the period of neutral  childhood  - allergic reactions, somatic  diseases, antibiotic treatment, enterobiosis and childhood  masturbation, children in the period of acute  respiratory viral infections, inability to take  care of the genitals; in adolescent girls - the presence of chronic somatic inflammatory diseases, antibiotic therapy,  early onset of sexual activity, lack of contraception, non-compliance with personal  hygiene  rules, violation of menstrual hygiene,  belated access to a doctor. The main causative agents of vulvovaginitis in the period of neutral childhood were representatives of coccal flora and E. coli, in adolescence - Candida and microbial associations. Conclusion. Preventive conversations with patients and their parents about the identified risk factors for vulvovaginitis are necessary in order to prevent the development of inflammatory diseases of the genitals and to preserve reproductive health.